Factors influencing reproductive choices of HIV positive individuals attending primary health care facilities in a South African health district - Samuel Agbo; Laetitia C. Rispel (BMC, 2017)
Abstract Background There is global recognition of the reproductive health rights of people living with HIV (PLHIV). The aim of this research study was to explore the reproductive choices, and the factors influencing these choices, of HIV positive patients attending primary health care (PHC) facilities in the Ekurhuleni health district of the Gauteng Province of South Africa. Methods During 2013, a cross-sectional survey was conducted in the Ekurhuleni health district. At each of three randomly selected community health centres, a random sample of HIV positive patients was selected. After informed consent was obtained, trained fieldworkers administered a structured questionnaire that elicited information on socio-demographics, reproductive choices and knowledge of reproductive options. Survey data were analysed using STATA® 13. Results The majority of survey participants (n = 430) were female (70%) and unemployed (57%). The mean age of participants was 36.4 years (SD 8.6): 40.8 years (SD 8.7) for men and 34.5 years (SD7.8) for women. Among survey participants, 46% expressed a desire for children (95% CI: 41.4-50.9). In the multiple logistic regression analysis, predictors of desire for children were age less than 49 years, marriage or living together, and no biological children. The odds of wanting children was 16.48 [95% CI: 5.94-45.74] times higher for PLHIV without children, compared with those with two or more children, while for those less than 25 years, the odds of wanting children was 0.78 [95% CI: 0.23-2.59] compared with those older than 50 years. The PLHIV knowledge on the available reproductive options was limited, with the majority relying on the guidance of the health workers. Conclusion Health care providers at PHC level should be educated to address the reproductive health needs of PLHIV. These aspects should be reflected in provincial and national health policies.